Comparación de la eficacia de los Sistemas Operativos Kali Linux y Parrot Os en la seguridad de redes en la Unidad Educativa Babahoyo. - Carreño Naranjo, Cesar Ariel (2024)
Information security is crucial today due to the rise of cyber threats such as malware, ransomware, and phishing attacks. Protecting data and systems requires a combination of preventive and reactive measures, including the use of firewalls, antivirus, and operating systems for network security, as well as constantly updating software that helps mitigate risks. Network security is a field that focuses on protecting the integrity, confidentiality, and availability of information and resources on a computer network. It involves a series of practices, tools, and technologies designed to prevent, detect, and respond to cyber threats and attacks. Kali Linux and Parrot OS are two popular operating systems in the network security arena, each with its distinctive features. Kali Linux is known for its focus on penetration testing and security analysis. It comes with a wide range of pre-installed tools that allow for thorough network and system audits. On the other hand, Parrot OS offers a similar suite of tools for security and privacy, but with an added focus on identity protection and forensic analysis. Parrot OS provides a friendly user interface and an optimized working environment for forensic analysis and software development. It stands out for its focus on privacy, which masks network traffic, and its integration with advanced analysis tools.